The right to be heard: towards a general principle of administrative law - P. A. Kuryndin (Правоприменение)
The subject of the article is related to the analysis of Russian legislation formation of opportunities for an individual to be heard, reflected in judicial practice.Methods. This analysis is based on the right to be heard as a general principle of administrative law, taken from foreign legal orders through the comparative legal method. In addition, the article used formal-dogmatic, historical methods. Initially, the guarantee in question is of a judicial nature, that is, it appeared and was further clarified in judicial practice. The lead in substantiating the right to be heard belongs to the Anglo-American legal family, since there has always been a special emphasis on procedural aspects. Along with this, French administrative law was not an exception, where the opportunity to be heard was also introduced by the State Council, but enshrined much later in the Code on regulating relations between the population and the administration. It should also be noted that the presence of a legislative act does not prevent the development of judicial doctrines.The purpose of this observation is to study the possible role of Russian judicial practice in the development of the right to be heard as a general principle of administrative law. To do this, it is necessary to determine the historical background for the emergence of this right, the development features in various legal traditions, to identify the features of Russian judicial practice, correlating them with foreign doctrines and associated concepts (primarily, with the right of participation).Main results. In Russian law, the right to be heard is provided by some federal laws. However, this principle has not yet been reflected in any act of higher judicial authorities, which could affect the level of protection by consolidated uniform approaches. The court decisions of the cassation instances presented in the study, on the contrary, show he discrepancies and shortcomings of legal regulation in disputes with citizens and in economic affairs. In the latter case, the legislation is more detailed; the courts apply it more readily, siding with private individuals. Whereas, within the framework of a personal reception of citizens, restoring rights is much longer and more difficult, because the administrative bodies themselves create various obstacles.Conclusion. These problems can be overcome through the perception of comparative legal approaches in understanding the right to be heard as a general principle of administrative law. Indeed, a private person should be able to present his point of view and evidence, especially when it comes to interference with his freedom.